Analysis of The Effect of Food Commodity Price Changes on Inflation in Central Java (Efficient: Indonesian Journal of Development Economics, 2025)
Commodity price movements have a significant impact on regional economic stability, especially in terms of inflation. In Central Java Province, fluctuations in the prices of rice, shallots, curly red chilies, red cayenne peppers, and cooking oil are the main causes of inflation. This phenomenon requires a more in-depth examination of the relationship between price fluctuations and inflation. This means that studies at the regional level are still limited. The purpose of this study is to analyze the impact of commodity price changes on inflation in Central Java. The data used is from 2021 to 2025 using the Autoregressive Distributed Lag (ARDL) - Error Correction Model (ECM) method. The data used is monthly secondary data obtained from the Central Statistics Agency (BPS) and the National Food Agency. The estimation results show that in the short term, the variables of curly red chili price, previous period curly red chili price, previous period rice price, and previous period cooking oil price have a significant effect on inflation, while in the long term, curly red chili price has a positive effect and rice price has a negative effect on inflation in Central Java. The CointEq(-1) coefficient, which has a value of -0.106705 and is significant, indicates the existence of a correction mechanism towards long-term equilibrium. This value suggests that around 10.67% of the deviation of inflation from its equilibrium in the previous period is adjusted or corrected during the current period.